Petrologic constraints of Cambrian mafic to intermediate volcanism in the Southern Oklahoma Aulacogen - Hobbs, Jasper (Kansas State University, 2015)
The Southern Oklahoma Aulacogen (SOA) produced more than 250,000 km[superscript]3 of Cambrian mafic to silicic magmatism, associated with the opening of the Iapetus Ocean. In the Arbuckle Mountains, oil and gas exploration showed mafic to intermediate volcanic rock interbedded with rhyolite lavas. The first description of these lavas was a result of the 1982 drilling of the Hamilton Brothers Turner Falls well. Cuttings have been collected from this well and five others, and whole rock major and trace element analysis, Sr and Nd isotope analysis, and rare earth element analysis has been completed on these samples. These samples plot primarily as tholeiitic to transitional basalts to andesites. Trace element ratios show Zr/Nb values ranging from 8-10, K/Nb values ranging from 300-600, and Ba/Nb values ranging from 10-20, which overlap with known EM1 OIB values. Applying a conservative age of 535 Ma for these rocks yields [superscript]87Sr/[superscript]86Sr[subscript]i values of 0.703970 to 0.706403 and epsilon Nd values of 1.67 to 3.22, which also fall within the accepted range of EMI values. [superscript]87Sr/[superscript]86Sr[subscript]i increases with wt. % SiO[subscript]2 and K/P, consistent with the generation of evolved compositions via open-system processes. The sample with the least radiogenic Sr isotope ratio, combined with its trace element ratios is most consistent with an EM1-type source. These results, coupled with existing isotope and trace element constraints from regionally exposed dikes and plutonic rocks that crop out in the Wichita Mts., give better insight into understanding what tectonic model (lower-mantle derived hotspot or extension of the lithosphere) drove the magmatic production of the SOA. The results are more consistent with a lower-mantle origin for SOA mafic-intermediate magmatism, and indicate the potential for flood basalt volcanism.
Keywords: Cambrian; Southern Oklahoma Aulacogen; Flood basalt; Large igneous province; Arbuckle Mountains; Basalt; Geochemistry (0996); Geology (0372); Petrology (0584)